Entre os morros e as figuras: gravuras rupestres no Parque Nacional Chapadas das Mesas, Carolina, Maranhão - Rocha, Danielly Morais (2016)
By mid-18th Century Rock Art (petroglyphs) in Maranhão, Brazil, was first registered by Yves d’Evreux, a french priest, who came to know about its existence from a speech of an indian witchdoctor. These petroglyphs were centuries later described and reproduced by naturalists. In spite of its remarkable importance, these symbolic pre-colonial remains located in the Center-South and South-West regions of the country have been scarcely studied. These rock art sites are part of an ample cultural context including landscape itself and its characteristics that reflect preferences and uses of ancient groups of people.It is probable that the choice for specific petroglyphs supports is related to the availability of suitable areas and the authors’ past landscape experiences and the sensorial aspects that emanate from it. This research work presents a phenomenological approach for the study of the Chapada das Mesas National Park rock art and landscape, so to understand how the sites are physically engaged and to identify features affecting the choice of supports by their materialization and insertion in the regional geomorphological context. So, it was developed a spatial analysis of the sites, paths and local borders, rock surfaces with art and its characteristics, water resources in different forms, the sites and art visibility and the landscape aspects related to perceptions and body movement. A visual register of the rock art was made through the use of digital technology, scanner Artec Eva 3D, producing data and contributing to the discussion about the technological advantages and disadvantages of such a method for documenting and analyzing archaeological remains.